2018
DOI: 10.1186/s12882-018-1092-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of inflammation-based prognostic scores on outcome in patients undergoing continuous ambulatory peritoneal dialysis

Abstract: BackgroundInflammation-based prognostic scores have been used as outcome predictors in patients with cancer or on hemodialysis. However, their role in patients on continuous ambulatory peritoneal dialysis (CAPD) remains unclear. This study aimed to examine the prognostic value of inflammation-based composite scores for mortality in CAPD patients.MethodsThis study was conducted in CAPD patients enrolled from January 1, 2006 to December 31, 2014 and followed until December 31, 2016. Three inflammation-based prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Didier et al 32 reported that the level of CRP was linked to the prevalence of microinflammation in PD patients, and they confirmed that a high CRP level was an independent risk factor for CVD events in PD patients. Furthermore, Liu et al 20 found that as a more sensitive inflammation masker, a high hs‐CRP level during follow‐up was identified as an independent predictor of mortality in PD patients, and every 1 mg/L increase in the hs‐CRP level was independently predictive of a 1.4% increase in mortality.In addition, other studies have proven that some combinations of several single markers in the forms of ratios or scoring systems proposed in recent years, such as the Glasgow prognostic score (GPS), 33 neutrophil‐to‐lymphocyte ratio (NLR) 34 and platelet‐to‐lymphocyte ratio (PLR), 35 are associated with mortality in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Didier et al 32 reported that the level of CRP was linked to the prevalence of microinflammation in PD patients, and they confirmed that a high CRP level was an independent risk factor for CVD events in PD patients. Furthermore, Liu et al 20 found that as a more sensitive inflammation masker, a high hs‐CRP level during follow‐up was identified as an independent predictor of mortality in PD patients, and every 1 mg/L increase in the hs‐CRP level was independently predictive of a 1.4% increase in mortality.In addition, other studies have proven that some combinations of several single markers in the forms of ratios or scoring systems proposed in recent years, such as the Glasgow prognostic score (GPS), 33 neutrophil‐to‐lymphocyte ratio (NLR) 34 and platelet‐to‐lymphocyte ratio (PLR), 35 are associated with mortality in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, commonly accepted nutritional markers, such as serum albumin (ALB) level, serum creatinine (Cr) level, hemoglobin (Hb) level, and body mass index (BMI), might be used to assess prognosis of patients with chronic kidney disease (CKD) [5,6]. However, other studies reported a poor predictive value of serum ALB, serum Cr, and other characteristics of PD patients for all-cause mortality or cardiovascular outcomes [7,8]. Furthermore, the prognostic values of various physiological ions have not been well determined [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A similar association was also indicated in patients undergoing continuous ambulatory peritoneal dialysis (CAPD). Cai et al ( 28 ) conducted a retrospective cohort study of 1,501 patients with CAPD and found a robust and consistent association between lower PNI value (<45) and overall mortality or CVD mortality that was independent of other common risk factors (HR=1.82; 95% CI, 1.36-2.43; HR=1.63; 95% CI, 1.06-2.51). Additionally, PNI was a prognostic factor in patients undergoing kidney transplantation and in patients undergoing peritoneal dialysis ( 25 , 29 ).…”
Section: Discussionmentioning
confidence: 95%